Merawat Jenggot Berdasarkan Ajaran Nabi pada Konteks Zaman Sekarang - Muhammad Sabir,; Asyraf, M. Asyraf Mubarak Sudarmin; Fajril Husni,; Abdullah, (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
The culture of beard grooming has been prevalent since ancient times, even before the advent of Islam. According to various stories, beard grooming was a common practice among the previous Prophets, Pharaoh, the Romans, Greeks, and other cultures. However, once Prophet Muhammad ordered Muslims to trim their mustaches and take care of their beards, it became a distinctive feature of Muslims and was useful as an identity in times of war. Despite the historical significance of beard grooming in Islam, it has become a trend in the current era among people of different religions, not just Muslims. This has led to the need for an in-depth study of the Prophetic Hadith to understand its relevance to the current conditions and situations. In addition, there is a word of command in the Prophet's Hadith about grooming beards, making it necessary to analyze and understand its true meaning and significance. This paper aims to conduct a qualitative research study based on literature searches to describe the history related to caring for the beard, express the opinions of scholars, and analyze it so that the Hadith about caring for the beard can be implemented in today's era.